Crop simulation analysis of phenological adaptation of chickpea to different latitudes of India - Vadez, Vincent; Soltani A; Sinclair, Thomas R. (Elsevier, 2013)
Plant phenology is a critical component of crop adaptation, especially under environmental conditions that don’t allow crop growth for unlimited periods. In chickpea (Cicer arietinum L.), which faces terminal drought and increasing temperature at the end of its growing season, it is widely considered that longer duration genotypes are needed for the higher latitudes of India and shorter duration genotypes for lower latitudes. Here, we compare two sets of genotypes bred in two locations varying in latitude (high latitude: Hisar, Haryana, India; low latitude: ICRISAT, Andhra Pradesh, India) for the number of biological days from emergence to flowering (EMR1) and for the grain filling period (R5R7). Biological days referred to days where the phenological development was optimal and therefore provides a measure of thermal time. Using a robust crop simulation model, the optimum EMR1 and R5R7 were determined for various locations. As expected, EMR1 and R5R7 values of genotypes bred for low latitude were lower than those bred for high latitude. However, predicted yields of these two sets of genotypes were similar when simulated for each of the two environments, yields being overall higher at Hisar. Results for the combined set of genotypes at each location predicted a similar optimum EMR1 to achieve maximum yield at each location: 44.3 biological days at Hisar and 43.5 biological days at ICRISAT. Derivation of optimum EMR1 across a total of ten locations in India indicated a wider range (37.2–51.8 biological days), although in eight locations the optimum EMR1 was in a narrower range (39.4–47.3 biological days). The differences in EMR1 across locations did not correspond to their latitudinal differences. Instead, rainfall through the growing season was significantly and positively related (R2 = 0.55) to optimum EMR1. These results indicate that the breeding for optimum EMR1 of chickpea in India needs to be focused on expected rainfall for a region, and that an optimum EMR1 of about 43 biological days would likely fit most of the environments.